PENGARUH RETURN ON EQUITY (ROE) DAN KEBIJAKAN HUTANG TERHADAP HARGA SAHAM DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA (ISSI) - Tiara Veliya Nur Kharisma; Mellya Embun Baining; Achyat Budianto (Yayasan Nusantara Hasana Berdikari, 2026)
This thesis aims to determine and analyze the influence of ROE and DER partially and simultaneously on PBV, to determine the influence of ROE, DER and PBV partially and simultaneously on stock prices and to determine the influence of ROE and DER partially on stock prices through PBV as an intervening. This research is a quantitative study using panel data. Data collection uses document techniques. The results of the study are: 1) ROE has an effect on PBV, 2) DER has no effect on PBV. 3) Simultaneously ROE and DER have an effect on PBV. 4) ROE has an effect on Stock Price, 5) DER has no effect on Stock Price, 6) PBV has an effect on stock prices, 7) Simultaneously, ROE, DER and PBV have an effect on stock prices, 8) PBV can mediate the effect of ROE on stock prices, and 9) PBV cannot mediate the effect of DER on stock prices.